Isoorientin alleviates ovalbumin-stimulated allergic rhinitis in mice by restoring Th1/Th2 balance - Huang, Jianyi; Ji, Ran; Qian, Xueshen; Shen, Yuli (Allergologia et Immunopathologia, 2024)
Allergic rhinitis (AR) is a chronic, non-infectious inflammatory condition of the nasal mucosa mediated by IgE. There is a need for the development of novel medications to treat this ailment. Isoorientin is a naturally occurring flavonoid that possesses antioxidant, anti–inflammatory, and various other advantageous characteristics. However, its potential effects on AR remain unclear. This study evaluates the therapeutic effects of isoorientin on ovalbumin (OVA)-induced allergic rhinitis (AR) in mice and explores the underlying mechanism. Our study revealed that isoorientin administration effectively decreased the frequency of nose rubbing and sneezing in AR mice. The groups treated with isoorientin showed a significant decrease in serum levels of IgE and histamine, with reductions of 40% and 30%, respectively. Isoorientin ameliorated inflammation of the nasal mucosa and restored the Th1/Th2 balance. In addition, isoorientin inhibited the activation of the NF-κB pathway in nasal tissues. In summary, Isoorientin alleviates OVA-stimulated AR in mice by restoring Th1/Th2 balance and blocking the NF-κB pathway. Thus, isoorientin exhibits promise as a natural therapeutic agent for allergic rhinitis.